An Empirical Test of the Relationship between Exchange Rate, Interest Rate and Inflation in Five African Countries from 1980 To 2012 (Global Journal of Management and Business Research, 2020)
The study examines the empirical relationship between exchange rate, interest rate and inflation in the context of Sub -Sahara African countries using panel data over 1980-2012 periods. The estimated values of the pooled, fixed and random effects models reveal identical results that interest rate and inflation maintain a monotonous relationship with the exchange rate, though the relationship is insignificant for interest rote only in the random effect model based on 1% level of significance. However; the result of the Hausman Test shows that the random effect model is not appropriate rather, the fixed-effect model is preferred. Based, on the Johansen Fisher panel co integration approach, a long-run relationship is established among the specified variables. Finally, it was discovered that the interest rate is weakly exogenously determined in the selected-countries throughout the freely and managed floating exchange rate systems.
Keywords: fixed effect; random effect; pooled data; panel cointegration; african countries